Audience Awareness Experience of the Representation of Silence in Erha's Advertisement 'No Noise, No Gimmicks': A Phenomenological Analysis by Edmund Husserl - Kumoro, Shinta Dewi (PINISI Discretion Review, 2025)
This study examines the audience’s lived experience and consciousness in interpreting silence as represented in the Erha Dermatology advertisement “No Noise, No Gimmicks” using Edmund Husserl’s phenomenological approach. Amid the dominance of symbolic noise in contemporary marketing communication, this advertisement adopts a contrasting strategy by positioning silence and simplicity as its core message. Employing a qualitative phenomenological methodology, data were collected through observation, in-depth interviews, and documentation involving six purposively selected participants. Data analysis followed Husserlian phenomenological stages, including phenomenological reduction, imaginative variation, and synthesis of meaning, to reveal the essential structure of audience experience. The findings indicate that silence is not perceived as the absence of communication, but as a meaningful phenomenon that evokes reflection, generates a sense of calmness, and constructs perceptions of honesty and brand authenticity. Silence functions as an active communicative medium that enables audiences to engage reflectively with the advertisement beyond verbal persuasion and visual intensity. This study concludes that silence-based communication offers an alternative advertising strategy by foregrounding audience consciousness as a central source of meaning-making and trust formation toward the brand.